A Jewish View of Assisted Dying. Issue 2 (1st January 2015) - Romain, Jonathan
Abstract: The essay explores assisted dying from a Jewish perspective. The author, Jonathan Romain, reveals that although the topic is currently in the news, it dates back to biblical times. He traces references there and in later rabbinic literature, which hints that it is permissible to hasten a person's death in order to prevent suffering, albeit passively. This leaves open the vexed question of whether active intervention can be condoned, and Romain examines the attitude of modern rabbis - from Orthodox to Reform traditions - as well as the Falconer Bill to permit assisted dying, concluding with a sympathetic appraisal.